EURO-MUSCULUS/USPRM Dynamic Ultrasound Protocols for Elbow - Ricci, Vincenzo; Güvener, Orhan; Chang, Ke-Vin; Wu, Wei-Ting; Mezian, Kamal; Kara, Murat; Leblebicioğlu, Gürsel; Pirri, Carmelo; Ata, Ayşe Merve; Dughbaj, Muhammad; Jain, Nitin B; Stecco, Carla; et al. (American journal of physical medicine & rehabilitation, 2022)
In this dynamic protocol, ultrasound examination of the elbow using different maneuvers is described for several/relevant elbow problems. Scanning videos are coupled with real-time patient examination videos for better understanding. The authors believe that this practical guide-prepared by an international consensus of several experts (EURO-MUSCULUS: European Musculoskeletal Ultrasound Study Group and USPRM: Ultrasound Study Group of ISPRM [International Society of Physical and Rehabilitation Medicine])-will help musculoskeletal physicians perform a better and uniform/standard approach.
Keywords: Elbow; Physical and Rehabilitation Medicine; Musculoskeletal Diseases; Musculoskeletal System; Ultrasonography; rehabilitační lékařství; ultrasonografie; Humans; loket; lidé; muskuloskeletální systém; muskuloskeletální nemoci